EFFECTS OF MAGNETIC FIELD ON PRE-TREAMENT OF SEEDLINGS AND GERMINATION - Iderawumi, Abdulraheem Mukhtar; Friday, Charles Eneminyene (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
Magnetic field studies have been a very important tool for exploring the electronic structure of condensed matter systems. Although applied magnetic fields in many cases have a relatively small effect on the overall electronic structure, they enable experimental techniques that can reveal properties of the underlying electronic structure that would be otherwise inaccessible. In other cases, magnetic field effects can be strong enough to drastically change the nature of the electronic state itself. Currently, cost of magnetic field generating equipment and modest increases in plant growth parameters observed in this study are limitations for the adoption of this technology for commercial plant production. In the future, further research may allow development of optimal magnetic field treatments for each plant species as well as more cost efficient magnetic field generating equipment.